On cycle-irregularity strength of ladders and fan graphs - Faraha Ashraf; Martin Baca; Andrea Semanicova-Fenovcikova; Suhadi Wido Saputro (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2020)
A simple graph G = (V(G),E(G)) admits an H-covering if every edge in E(G) belongs to at least one subgraph of G isomorphic to a given graph H. A total k-labeling φ : V(G) ∪ E(G) → 1,2,..., k is called to be an H-irregular total k-labeling of the graph G admitting an H-covering if for every two different subgraphs H' and H